KARAKTERISTIK SOSIODEMOGRAFI KASUS MALARIA DI PROVINSI RIAU TAHUN 2018-2022 - Murtono, Heru; Dewi, Oktavia; Anusirwan, Anusirwan (Ensiklopedia of Journal, 2024)
The problem of Malaria cases in Riau Province in the last 5 years. It is known that there was a significant increase in malaria cases (outbreak) in Riau Province from 2019 which amounted to 148 cases to 1774 cases in 2020 and further increased in 2022 to 1811 cases. The purpose of the study was to determine the description of malaria cases in Riau Province in 2018-2022. The research method uses descriptive quantitative research using secondary data in the form of Malaria case reports in Riau Province in 2018-2022 by looking at the number of cases by district / city, gender, age group, and by type of work. The results showed that according to gender, the number of confirmed positive malaria cases in men was greater than the number of confirmed positive malaria cases in women, according to age groups showed that over 5 years, the number of confirmed positive malaria cases in the 12-25 year age group and 26-45 years was greater than the other age groups and according to occupation showed that in 5 years, the highest number of confirmed positive malaria cases occurred in Rokan Hilir Regency. It is known that people who have not worked or are not working, followed by housewives and fishermen are the types of jobs with the highest malaria cases in 2018-2022. It is expected that the community will always clean stagnant water around the house, use mosquito repellent when on the move.Keywords: Gender, Malaria, Occupation